Toll-like receptor 3 -926T>A increased the risk of breast cancer through decreased transcriptional activity. (2nd December 2019) - Fan, Lei; Zhou, Peng; Chen, Ao-Xiang; Liu, Guang-Yu; Yu, Ke-Da; Shao, Zhi-Ming
ABSTRACT: Toll-like receptor 3 (TLR3) is a viral sensor that induces apoptosis in response to double-stranded RNA (dsRNA). Common genetic changes in the TLR3 gene may influence breast cancer susceptibility and development. However, all of the polymorphisms in the previous study were only markers of the TLR3 gene, not causative polymorphisms. In this study, we performed a case-control study focusing on the relationship between rs5743305 (−926T>A), a single nucleotide polymorphism (SNP) in the promoter region of TLR3, and breast cancer. We found that the genetic variant rs5743305 increased the risk of breast cancer under the dominant and codominant models (dominant model: AT+AA vs TT.: OR = 1.3023, 95%CI: 1.0778–1.5736, P = .0062; codominant model: AA vs. TT: OR = 1.3919, 95%CI: 1.0177–1.9036, P = .0384; AT vs. TT: OR = 1.2799, 95%CI: 1.0475–1.5639, P = .0158) but not under the recessive model (TT vs. AT+AA, OR = 1.2387, 95%CI: 0.9197–1.6682, P = .1588). The same trends were found in the age-adjusted logistic regression study and stage 2 study. Furthermore, the electrophoretic mobility shift assay (EMSA) and luciferase reporter assay showed that rs5743305 decreased the transcriptional activity of TLR3. There was consistently reduced TLR3 mRNA and protein expression in human breast cancer samples from patients with TLR3 − 926A. Therefore, TLR3 rs5743305 increases the risk of breast cancer by decreasing the transcriptional activity of TLR3. This study may provide a better understanding of the genetic architecture underlying disease susceptibility and may advance the potential for preclinical prediction in future genetic testing.